PENERAPAN PERILAKU DISIPLIN PADA ANAK KELOMPOK A DI TK KRISTEN IMMANUEL PONTIANAK - Lusina, Lusina; Ali, Muhamad; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the application of disciplinary behavior in children in group A in Pontianak Immanuel Christian Kindergarten. The research method used is descriptive with a qualitative approach research. The source of this research data is the children of group A and the data are the classic A group interviews, children's observation sheets, direct observation of children, interviews with teachers, and teacher observation sheets for children in group A.The results of the study showed that in the application of teacher disciplinary behavior, they gave good direction and always reminded children to behave discipline through regulations, consistency, punishment, and appreciation, but children were still less disciplined as there were those who arrived late to school, littering, could not pack the toy, and can't queue when washing hands.This is evidenced by 158 children from A1 to A6, there are 31 children who still need guidance and direction in disciplined behavior so that children can understand, remember, and accept what is allowed and not to be done so that children are accustomed to disciplined behavior both at home and at school . Keywords: Discipline Behavior, Child group A.